The ecology and natural history of Chilean saltmarshes - Fariña, José Miguel; Camaño, Andrés (Springer, 2017)
This book consolidates the information, results, experience and perspectives of different research groups working on Chilean Saltmarshes. Some aspects of these ecosystems such as their bio-geographical connectivity, flora and faunal components, the interaction between ecosystem components and especially the response of this kind of ecosystems to human and natural perturbations defines the Chilean Saltmarshes as an attractive systems for future studies, focused into test the theoretical and experimental aspects of saltmarshes and general ecology.
Keywords: Salt marsh ecology -- Chile.; Salt marshes -- Chile.; Chile.; elektronické knihy; electronic books